A microlattice material with negative or zero thermal expansion. (December 2017) - Jin, Z.-H.
Abstract: This work presents a microlattice composite structure with a cubic unit cell that consists of twelve quarter-octahedra and describes an investigation of thermal expansion behavior of the proposed lattice material. It is assumed that all edge members of the octahedron have the same material properties and the members connecting the opposite vertices of the octahedron have different properties. Thermal expansions along the unit cell edge directions are determined by means of thermoelasticity. It is shown that the lattice material may undergo negative or zero thermal expansion with proper selection of the material and geometric properties of the microlattice members. Highlights: A microlattice composite material with a cubic unit cell is designed. The lattice material can experience negative or zero thermal expansion. The strains of the composite are linearly dependent on the temperature variation. The microlattice members deform both mechanically and thermally.